PEMBUATAN PROGRAM APLIKASI BERBASIS WEBSITE PADA YAYASAN POUK BOJONG INDAH, JAKARTA - Riani Riani; Jap Tji Beng (Jurnal Ilmu Komputer dan Sistem Informasi, 2016)
Website is an internet services application much sought after at the moment. The number of users on the website currently utilized by organizations as the media dissemination of information as well as media promotion. The utilization of this website not only carried out by organizations that are non-profit, but there is also a non-profit. One of the organizations that are non-profit and want to make use of the website as a medium of information dissemination is Yayasan Persekutuan Oikoumene Umat Kristen (POUK) Bojong Indah. The methodology used in this software development is a method of prototyping. The reason the use of prototyping model this is because the application can be done easily. People who need an application knowing what to expect in the application program, and save time in the development of the system. This website-based application program will be created using the programming language PHP and Javascript. The management of the database on this website-based applications use MySQL with Apache as the server software. The purpose of the creation of application programs based on website yayasan POUK Bojong Indah is to help Yayasan POUK Bojong Indah in distributing information relating to the schedule of activities, news about Yayasan POUK Bojong Indah, profils, and activities undertaken.